Pelaksanaan Lelang Barang Jaminan Debitur Berdasarkan Undang-Undang Hak Tanggungan Nomor 4 Tahun 1996(Studi Kasus Di Kantor Pelayanan Kekayaan Negara Dan Lelang Surakarta) - Nur Samsu Ridwan, Dwi; , Nuswardhani, S.H.,S.U; , Shalman Al-Farazi, SH.,M.H.,M.Kn (2016)
Based on this study showed that guarantees a security interest has provided three kinds of options for the implementation of the execution is in the form parate execution as defined in Article 6 UUHT parate execution in the security rights is an execution without the intervention of the court but appealed directly to the office auction of the State to conduct auctions to security object security right to take on debt repayment of the debtor . And there are barriers experienced by the offices of State assets and auction Surakarta ( KPKNL ) that the limit price auction only put the interests of creditors , lawsuits resistance of oemberi security rights , there are technical constraints in terms of execution , difficulty empties objects encumbrance and difficult to find buyers auction. This study is expected to be input for offices and auction Surakarta State assets , debtors and creditors to the dispute.